PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS AUGMENTED REALITY UNTUK CIPTA SENI DAN GERAK BAGI SISWA SEKOLAH DASAR - Maitris Yulida; Rika Irawati; Silviana Evi Vitriani Taileleu; Fransiska Eka Tri Lestari; Ardipal; Desyandri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The use of conventional learning media in elementary schools, particularly for Arts and Movement (Seni dan Gerak) subjects, remains limited to textbooks and blackboards, resulting in low student engagement and difficulty visualizing dance movement concepts. This study aims to develop Augmented Reality (AR)-based interactive learning media for Arts and Movement Creation (Cipta Seni dan Gerak) for elementary school students to meet the criteria of validity, practicality, and effectiveness. The research employed the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). Data were collected through expert validation questionnaires, teacher and student practicality questionnaires, as well as pretest-posttest instruments. The study was conducted at three elementary schools in Sikakap District: SDN 21 Makalo, SDN 35 Matobe, and SDN 15 Sikakap, involving 24 fifth-grade students. Results showed that expert validation reached 90.5% (very valid); practicality assessment from teachers and students achieved 89.5% (very practical); and the N-Gain score was 0.61, classified as moderate-high effectiveness. Comparisons with conventional media confirmed that AR media significantly improved active student involvement from below 40% to 87.5% task completion. This study concludes that AR-based Cipta Seni dan Gerak learning media is valid, practical, and effective for use in elementary schools in remote areas.